Cochrane Review Summaries—January 2020. Issue 1 (January 2020) - Haas, David M.; Kumar, Nimisha; Jahanfar, Shayesteh
Abstract : With this issue, the journal launches a new feature titled "Cochrane Review Summaries." This feature highlights recently published Cochrane Reviews of interest to the readers of Obstetrics & Gynecology . The brief summaries are published below, and the complete references, with hyperlinks to the full Cochrane Review, are listed in Box 1 .